The gorgon's fury - Mull, Brandon, 1974- (Mull, Brandon, 1974- Tales of Newel & Doren, 2025)
"Everyone's favorite satyrs are back at Fablehaven after helping Dragonwatch put an end to the dragon rebellion. There's a new threat at Fablehaven when a few unlucky inhabitants, including some of their fellow saytrs, have been found petrified and turned to stone. Could a rampaging gorgon be on the loose? Satyrs Newel and Doren travel from Fablehaven to Key West, Florida to seek counsel from the Listening Doll (a talisman with the power to reveal the antidote for any magical malady) on how to stop a dangerous gorgon--and win the annual Satyrs Games"--